Factors affecting the early establishment of neonatal intestinal flora and its intervention measures - Ma, Guangyu; Shi, Yuguo; Meng, Lulu; Fan, Haolong; Tang, Xiaomei; Luo, Huijuan; Wang, Dongju; Zhou, Juan; Xiao, Xiaomin (Frontiers in Cellular and Infection Microbiology, 2023)
In recent years, it has become evident that early-life intestinal flora plays a pivotal role in determining human health. Consequently, it is imperative to explore the establishment of neonatal intestinal flora and its influencing factors. Early neonatal intestinal flora is influenced by a multitude of factors, including maternal and infant-related factors, as well as external environment. This review summarizes the colonization mechanism of intestinal flora in the early life of newborns and discussed their influence on the establishment of neonatal intestinal flora, taking into account factors such as delivery mode, gestational age and feeding mode. Additionally, this review delves into the natural or artificial reconstruction of intestinal flora colonization defects in infants born via cesarean section and premature infants, with the goal of establishing a theoretical foundation for preventing and treating issues related to neonatal intestinal flora colonization and associated diseases.